Psoriasis Susceptibility 1 Candidate 1 (PSORS1C1) Polymorphism is Associated with Autoimmune Thyroid Disease in a Chinese Han Population. (4th July 2022) - Jiang, Yanfei; Mao, Xudong; Song, Ronghua; Mu, Kaida; Yang, Yanping; Zhang, Jin-an
ABSTRACT: Background: Autoimmune thyroid disease (AITD) is an inherited, complex gene- and immune-related disorder that mainly includes Graves' disease (GD) and Hashimoto's thyroiditis (HT). Psoriasis susceptibility 1 candidate 1 ( PSORS1C1 ) is a susceptibility gene associated with many autoimmune diseases, but its role in an individual's predisposition to AITD is unknown. Methods: This study included 1065 Chinese Han patients with AITD and 943 matched healthy individuals. The rs3130983, rs3778638, rs3815087, and rs4959053 single nucleotide polymorphisms (SNPs) in PSORS1C1 were determined using multiplex polymerase chain reaction technology. Results: Of the four SNPs, only the distribution of the rs3778638 genotypes was different between the AITD (AA, 2.67%; AG, 19.15%; and GG, 78.18%) and control (AA, 1.52%; AG, 22.2%; and GG, 75.87%) groups ( P = .046). An association between rs3778683 and GD was observed ( p = .039) but not with HT. No linkage disequilibrium was observed for rs3130983, rs3815087, rs3778638, and rs4959053 in PSORS1C1 among the patients with AITD and controls. Conclusion: This study suggests the influence of PSORS1C1 rs3778638 on the susceptibility to GDs, supporting this locus as a common autoimmunity risk factor.